Analisis Variabel Sosial Media Marketing, Optimasi Mesin Pencari, dan Interaksi Konsumen Online terhadap Pertumbuhan Penjualan Produk Kerajinan Tangan di Kota Bandung - Lita Limpo; Eva Yuniarti Utami (Jurnal Ekonomi dan Kewirausahaan West Science, 2024)
This study investigates the effect of digital marketing strategies, including social media marketing, search engine optimization (SEO), and online consumer interaction, on the sales growth of handicraft products in Bandung City. A quantitative approach was employed, and data were collected from 135 handicraft businesses through structured questionnaires. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results revealed significant positive relationships between social media marketing, SEO, online consumer interaction, and sales growth. Specifically, social media marketing, SEO, and online consumer interaction were found to have a significant positive impact on sales growth, highlighting the importance of leveraging digital marketing channels effectively in the handicraft industry. These findings provide valuable insights for handicraft businesses in Bandung City and contribute to the broader understanding of digital marketing's role in driving sales growth.